Tasting the Bedrock - Elder, John (Cuizine)

(untitled) (McGill University Library, 2010)
This article begins with a personal narrative of the author’s involvement in sugaring before moving to an account of collaboration with local experts in maple production and testing, "sensory analysis," and geology to explore the correlation between the taste of syrup from particular sugarbushes and such factors as the bedrock on those sites. This high-spirited and stimulating investigation was inspired in part by collaborator Amy Trubek’s application of the concept of terroir to a wide range of foods beyond wine. Although it at one point alarmed Vermont's maple industry, it has ultimately led to a productive dialogue, to which authorities from the state's Agency of Agriculture as well as maple researchers and producers in Quebec have all contributed. Grounded in a small-scale operation in Starksboro, Vermont, the article ultimately points toward both innovations and marketing opportunities within a much wider circle.